Internal Control Effectiveness in Malaysian Cooperatives: Insights from SelfOrganizing Maps and Artificial Neural Networks - Shamsul Anuar, Abd Rahim; Intan Salwani, Mohamed (Journal of Cultural Analysis and Social Change, 2025)
The study aims to evaluate and visualize the effectiveness of internal control in Malaysian cooperatives. Adapting the three categories of internal control objectives and the five internal control components in the internal control integrated framework designed by COSO, the effectiveness of internal control is measured based on assessments conducted by the cooperative’s internal auditor or audit committee member, as Malaysian cooperatives are not required to provide material weakness statements in financial reporting. Survey data from 126 cooperatives generating Malaysian Ringgit (RM) 800,000.00 and above are clustered using the self-organizing map (SOM), a clustering technique based on artificial neural networks (ANNs). The analysis reveals four groups of internal control effectiveness in Malaysian cooperatives, visually demonstrating the association between internal control components and objectives. The results suggest an interrelated, albeit not straightforward, relationship between internal control components and objectives. The study emphasizes the importance of heightened attention to internal control within Malaysian cooperatives by responsible parties, including internal auditors, internal audit committees, cooperative management, cooperative boards, and the Malaysian Cooperative Society Commission (Mcsc). This paper represents one of the first attempts to assess internal control components and objectives in Malaysian cooperatives based on internal audit and audit committee assessments rather than relying on material weakness statements.